أولويات الإصلاح في فكر سعيد النورسي دراسة استقرائية لـ"رسائل النور" - عثمان, م.د.ئاراس حمه أمين (Sulaimani Journal for Humanities, 2023)
Sa'id Nursi (1876-1960), a prominent Kurdish intellectual, was born during a period of great turmoil. He was a learned scholar and philosopher who dedicated his life to serving Islam and revitalizing religious and philosophical teachings. He played a significant role in engaging Muslims worldwide through his extensive writings and contributions. Sa'id Nursi's entire life was devoted to the service of Islam, promoting religious faith, philosophy, and socio-political ideas. He excelled in presenting Islamic teachings and addressing contemporary challenges, bridging the gap between European and Islamic civilizations. His works encompassed a wide range of topics, including the Quran, theology, ethics, and socio-political issues, with a fresh and comprehensive approach. Furthermore, Nursi was renowned for his remarkable expertise and intellectual prowess in various fields, particularly in the domain of religious revival and socio-political reform. He sought to reconcile reason, faith, and progress, employing a novel and balanced methodology. Moreover, Nursi made significant contributions in the field of Islamic education, advocating for a comprehensive educational system that encompassed religious studies, modern sciences, critical thinking, and practical application.